2016
DOI: 10.3390/su8040364
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the Limiting Issues Inhibiting Sustainability Embeddedness

Abstract: There can be little doubt that sustainability has become one of the most important issues in business in recent years. In spite of sustainability's importance, there is agreement amongst leaders and practitioners that sustainability is not as embedded as desired. This study reports a framework on inhibitors that limit sustainability embeddedness in organizations. The framework can assist management to address the non-achievement antecedents of embeddedness specifically and holistically. This study obtained emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…These challenges include conceptual ambiguity, too many narratives in practice, inherent unsustainability, investor bias and exhibiting stakeholder preferences (Thomson, 2014;Grey, 2010;Setia et al, 2015;Higgins et al, 2014). These were not intentionally omitted but rather explored as part of earlier, associated research (Le Roux and Pretorius, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…These challenges include conceptual ambiguity, too many narratives in practice, inherent unsustainability, investor bias and exhibiting stakeholder preferences (Thomson, 2014;Grey, 2010;Setia et al, 2015;Higgins et al, 2014). These were not intentionally omitted but rather explored as part of earlier, associated research (Le Roux and Pretorius, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, key to university engagement with the SDGs was the strategic alignment of the academic mission with sustainable development in its broadest definition (Rouxle and Pretorius, 2016). An effective means of framing this was to adopt a "living lab" model that can bring a range of projects under one governance framework.…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
“…To realize more fully the innovation potential of such an organization, new capabilities need to be built into the leadership and governance systems and processes to enable idea flow across and within the institution (Middlehurst, 2004; Cullen-Lester et al , 2016). However, the processes and structures through which strategy and decision making are effected are typically hierarchical and present a barrier to co-creation such that creativity and innovation are hindered (Kothari and Handscombe, 2007; Le Roux and Pretorius, 2016). Indeed, it has been suggested that “the corporation is at odds with the future” (McCracken, 2013) such that permeability to ideas is key to sustaining success (Pentland, 2015).…”
Section: Introductionmentioning
confidence: 99%